Jelajah Virtual Public Places Melalui Penggunaan Barcode Dalam Teks Interaksi Transaksional - Sri Suryanti (Jurnal Lingkar Mutu Pendidikan, 2021)
This study aims to improve the ability to express the students’ opinion in exploring the virtual of public places through barcodes. Through a qualitative approach, data collection was taken from 33 students in Class 7.06. The test of result data in cycles 1 and 2 experienced increasing in student learning outcomes which referred to the criteria of score minimum of 67, with description of the predicate A to D as follows: 1) needs to be maximized (D), 2) enough (C), 3) good (B), 4) excellent (A). Strengthening students' digital literacy skills in using barcodes through android applications, 87% succeeded in downloading the QR Code Scanner application, 13% failed to download due to limited HP memory capacity and internet quota. This research is expected to provide meaningful information for English teachers in learning transactional text material about public places to improve students' speaking skills as a learning tool that becomes a provision in real life in the surrounding environment